Survival outcomes and mobilization during venovenous extracorporeal membrane oxygenation: a retrospective cohort study - Rottmann, Felix A.; Noe, Christian; Bemtgen, Xavier; Maier, Sven; Supady, Alexander; Wengenmayer, Tobias; Staudacher, Dawid L. (Frontiers in Medicine, 2023)
Introduction Venovenous extracorporeal membrane oxygenation (V-V ECMO) can be considered in critically ill patient in severe pulmonary failure. However, the mobilization of patients on V-V ECMO can be challenging due to logistic and safety concerns. This study aimed to investigate whether 30 days survival was improved in patients who were mobilized during V-V ECMO support. Methods We conducted a retrospective cohort all-comer study that included all patients cannulated for V-V ECMO at a single center. Patients with a V-V ECMO duration below 24 h were excluded from the analysis. The patients were grouped based on the ICU mobility scale documented during V-V ECMO support. The primary endpoint was 30 days survival, and secondary endpoints included weaning from ECMO and mechanical ventilation, as well as hospital survival. Results A total of 343 patients were included in the study, with a median age of 56 years and 32% were female. Among them, 28% had chronic lung disease. The ICU mobilization scale ≥2 during ECMO was documented in 62/343 (18%) patients. There were no significant differences in age, gender and preexisting lung disease. Duration of ICU stay (13.1 vs. 15.6 days), time on ECMO (186 vs. 190 h) and mechanical ventilation (11.2 vs. 13.6 days) were slightly shorter in patients with ICU mobility scale <2 compared to those with ≥2 (all p = 0.0001). However, patients with ICU mobilization scale ≥2 showed significantly better 30 days survival (71.0 vs. 48.0%, OR 2.6 (1.5 to 4.8), p = 0.0012) compared to those with <2. In the ≥2 mobility scale group, a significantly higher number of patients were successfully weaned from the ventilator (61.3 vs. 46.6%, OR 1.8 (1.0 to 3.2), p = 0.049). A stronger correlation was observed between more intense mobilizations, such as being in a standing position (OR 5.0 (1.7 to 14.0), p = 0.0038), and higher 30 days survival. Conclusion The findings of this study suggest that active mobilization during V-V ECMO support is associated with improved 30 days survival and successful weaning from the respirator. Incorporating mobilization as part of the therapeutic approach during ECMO support may offer potential benefits for critically ill patients.